2017
DOI: 10.1080/19490976.2017.1299846
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics promote the sampling of luminal antigens and bacteria via colonic goblet cell associated antigen passages

Abstract: Bacterial translocation is defined as the passage of live bacteria from the gut lumen to distant sites. Gut commensal bacteria translocation has been attributed to ‘leakiness’, or ‘barrier breach’ of the intestinal epithelium, allowing live bacteria to cross an inappropriately permeable barrier and disseminate to distant sites. Alternatively, studies suggest dendritic cells directly capture luminal commensal bacteria and transport them to distant sites in the steady-state by extending dendrites between epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 43 publications
3
65
0
Order By: Relevance
“…i–k), indicating that CCR6 was promoting interactions with the epithelium. We never observed CD11c + cells extending dendrites into the lumen in wildtype or CCR6 −/− mice, consistent with prior observations that this is a rare event in the steady state when the mucus barrier is intact …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…i–k), indicating that CCR6 was promoting interactions with the epithelium. We never observed CD11c + cells extending dendrites into the lumen in wildtype or CCR6 −/− mice, consistent with prior observations that this is a rare event in the steady state when the mucus barrier is intact …”
Section: Resultssupporting
confidence: 92%
“…Evaluation of bacterial translocation to the MLN was performed as previously described . Mice were gavaged with 500 mg ampicillin, 500 mg metronidazole, 500 mg neomycin and 250 mg vancomycin and colon‐draining MLNs were isolated 4 days later.…”
Section: Methodsmentioning
confidence: 99%
“…S4). Studies evaluating TED formation in adult mice removed luminal contents and mucus prior to imaging (3032, 35, 36), a process, which induces TED formation in the SI, but not the colon of adult mice (34). We observed that even after removal of the luminal contents and mucus layer, TEDs did not form in the SI or colon of DOL18 mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, luminal exposure to an invasive S . Typhimurium, shut off GAP‐associated translocation suggesting that goblet cell sensing of an invasive pathogen to shut off GAPs is a host defence mechanism (Kulkarni et al ., ; Knoop et al ., ).…”
Section: The Microbiota Influences Gut Biologymentioning
confidence: 97%
“…Deletion of goblet cells in a mouse model of wild type Salmonella Typhimurium infection prevented the translocation bacteria to the draining mesenteric lymph nodes, indicating that S. Typhimurium uses goblet cells as an entry portal. Furthermore, luminal exposure to an invasive S. Typhimurium, shut off GAP-associated translocation suggesting that goblet cell sensing of an invasive pathogen to shut off GAPs is a host defence mechanism (Kulkarni et al, 2016;Knoop et al, 2017).…”
Section: Microbial Targeting Of Epithelial Immune Defencesmentioning
confidence: 99%